An exploration of the longer-term impacts of community participation in rural health services design. (September 2015) - Farmer, Jane; Currie, Margaret; Kenny, Amanda; Munoz, Sarah-Anne
Abstract: This article explores what happened, over the longer term, after a community participation exercise to design future rural service delivery models, and considers perceptions of why more follow-up actions did or did not happen. The study, which took place in 2014, revisits three Scottish communities that engaged in a community participation research method (2008–2010) intended to design rural health services. Interviews were conducted with 22 citizens, healthcare practitioners, managers and policymakers all of whom were involved in, or knew about, the original project. Only one direct sustained service change was found – introduction of a volunteer first responder scheme in one community. Sustained changes in knowledge were found. The Health Authority that part-funded development of the community participation method, through the original project, had not adopted the new method. Community members tended to attribute lack of further impact to low participation and methods insufficiently attuned to the social nuances of very small rural communities. Managers tended to blame insufficient embedding in the healthcare system and issues around power over service change and budgets. In the absence of convincing formal community governance mechanisms for health issues, rural health practitioners tended to act as conduits between citizens and the Health Authority. The study provides new knowledge about what happens after community participation and highlights a need for more exploration. Highlights: Explores what happens after a rural health community participation exercise. Includes multiple stakeholders, juxtaposing citizen and management perspectives. Highlights health practitioner role as a conduit for communication and change. Reveals a deficit in formal community governance around health issues. Shows that citizen can be 'responsibilised' to coproduce rural services.